2000
DOI: 10.1523/jneurosci.20-09-03328.2000
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Hemodynamic Blood Oxygenation Level-Dependent Response through Combination of Functional Magnetic Resonance Imaging and Optical Recording in Gerbil Barrel Cortex

Abstract: Fast, low-angle shoot functional magnetic resonance imaging (fMRI), based on the blood oxygenation level-dependent (BOLD) effect, was combined with optical recording of intrinsic signals (ORIS) and 2-deoxyglucose labeling in gerbil barrel cortex. We observed over the activated barrel a positive BOLD signal and increased levels of deoxyhemoglobin and total hemoglobin during each period of prolonged (30 sec) D2 vibrissal stimulation. These data show that the hemodynamic basis of this fMRI signal is not necessari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 80 publications
(111 reference statements)
3
66
0
Order By: Relevance
“…Indeed, the positive values of A P /A R obtained in this study indicate that an increase in the blood volume correlates with an increase in the BOLD signal, as does the decrease in [HHb]. At a magnetic field strength of 1.5 T, and using a TE of 40 ms, the values of the parameters k 1 , k 2 , and k 3 are approximately 2.8, 0.57, and 0.43, respectively (Hess at al., 2000). Therefore the values of A P /A R obtained here are in a relatively good quantitative agreement with the ratio (k 1 ϩ k 2 )/(k 2 ϩ k 3 ) ϭ 3.37.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Indeed, the positive values of A P /A R obtained in this study indicate that an increase in the blood volume correlates with an increase in the BOLD signal, as does the decrease in [HHb]. At a magnetic field strength of 1.5 T, and using a TE of 40 ms, the values of the parameters k 1 , k 2 , and k 3 are approximately 2.8, 0.57, and 0.43, respectively (Hess at al., 2000). Therefore the values of A P /A R obtained here are in a relatively good quantitative agreement with the ratio (k 1 ϩ k 2 )/(k 2 ϩ k 3 ) ϭ 3.37.…”
Section: Discussionmentioning
confidence: 56%
“…For this reason, the behavior of such important cerebral parameters as regional cerebral blood flow (rCBF), volume (rCBV), oxygenation (rCBO), and cerebral oxygen metabolic rate (CMRO 2 ) during cerebral activation remains controversial. In one study (Bandettini et al, 1997) the authors concluded that both rCBF and CMRO 2 remain constant during cortical activation, while other groups have reported significant changes in these parameters (Buxton et al, 1998;Feng et al, 2001;Hess et al, 2000). The basic idea of our work is to approach the problem by using two different measurement techniques, functional magnetic resonance imaging (fMRI) and nearinfrared spectroscopy (NIRS).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The result is a BOLD signal increase with no change in deoxyhemoglobin. This subtlety of the BOLD signal may become important in comparing fMRI data with optical or near-infrared results that are sensitive to deoxyhemoglobin and oxyhemoglobin: there is no one-to-one correspondence between the BOLD signal and the total deoxyhemoglobin (Hess et al, 2000).…”
Section: Alternative Forms For the Bold Signal Modelmentioning
confidence: 99%
“…Several applications of MR small animal brain image analysis like the generation of generic functional atlases or the combination of functional data from different modalities [1] rely on the comparison and combination of numerous images of the same or distinct specimens. In this context cerebral vascular MR angiograms play an important role as blood vessels can be used as excellent landmarks for image registration.…”
Section: Introductionmentioning
confidence: 99%